Pengaruh kualitas pelayanan terhadap keberhasilan koperasi melalui partisipasi anggota sebagai variabel intervening - Lila Putri Arum Sari Ibrahim; Hari Subiyantoro (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2020)
This study aims to determine the effect of service quality on member participation, determine the effect of service quality on the success of cooperatives and determine the effect of member participation on the success of cooperatives. This type of research is a quantitative study with a simple random sampling technique. The data collection method used a questionnaire which included three research variables, namely service quality, member participation and the success of the cooperative. Hypothesis testing uses path analysis with the help of AMOS 24 analysis tools. The results of the analysis show that service quality has a significant positive effect on member participation with a probability value of 0.000, which is smaller than the p value of 0.05. Service quality has a significant positive effect on the success of the cooperative with a probability value of 0.000 which is smaller than the p value of 0.05. Member participation has a significant positive effect on the success of the cooperative with a probability value of 0.047 which is smaller than the p value of 0.05.